Presentation of an Algorithm for Secure Data Transmission based on Optimal Route Selection during Electromagnetic Interference Occurrence - A. H. Poursoltan Mohammadi; M. Chehel Amirani; F. Faghihi (Institute of Advanced Engineering and Science, 2018)
This paper proposes a comprehensive algorithm for secure data transmission via communication conductors considering route optimization, shielding and data authentication. Using of appropriate coding method causes more efficiency for suggested algorithm during electromagnetic field attack occurrence. In this paper, MOM simulation via FIKO software is done for field distribution. Due to critical situation of malfunctioning of data transferring, appropriate shield is designed and examined by shielding effectiveness (SE) criterion resulted of MOM simulation; finally to achieve reliability of data security, MAC hash function is used for space with field attack probability, turbo code is employed.